Letter (copy) : Help for Spanish workers - Citrine, Walter, 1887-1983
030-0161-001 INTERNATIONAL. WMC/EAB/ 16th June 1938. Miss Barbara Barclay Carter, The People and Freedom Group, 35, Campden Street, W. 8. Dear Miss Carter, HELP FOR SPANISH WORKERS. In reply to your letter of the 14th instant asking whether it is possible for some financial assistance to be given to Basque refugees now resident in France, we have to inform you that the monies which are subscribed as a result of our appeal on behalf of the Spanish Workers are remitted to the International Federation of Trade Unions, 9, Avenue D'Orsay, Paris, VII. I would suggest, therefore, that you write to the General Secretary, Mr. Walter Schevenels, informing him of the request which you have received from the Basque Trade Unions. Yours sincerely, General Secretary. 292/946/30/161